A Proposed Model for "Competition" Factor as Moderator on the Influence to English Language Learning Quality of Students -- A Case of Higher Education in Vietnam - Diep, Le Thi Ngoc; Hieu, Tran Chi; Hieu, Vu Minh (The journal of language and linguistic studies, 2021)
Resulting from the Industrial Revolution 4.0, English is evolving into a global language and is detected from multi-aspects consisting of technological, scientific, and business aspects, and completely, English language learning quality must be enhanced. Thus, this paper focuses on constructing a conceptual framework in which competition is presenting as a moderator on the influence on the English language learning quality of students in the context of higher education in Vietnam. To achieve this objective, the paper employs a qualitative approach through tools of the meta-analysis, systematic review, from 86 publications as research papers, theses/ dissertations, books, and other relevant publications in the focused subject from prominent and reliable databases, including Google Scholar, Research Gate, Scopus, Web of Science, EBSCO, Cengage and Springer, etc. and direct observation with 55 English language classes, 5 interviews are conducted by using a semi-structured questionnaire with 135 students and 55 lecturers and 5 educational/ English teaching experts. The paper hopes to contribute to English learning quality enhancement and extends its contribution to the educational quality in higher education.